2006
DOI: 10.4049/jimmunol.176.10.5848
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Elicits Weak IFN-γ Memory Responses Compared with Respiratory Syncytial Virus

Abstract: Human metapneumovirus (MPV) is a recently discovered pathogen that causes repeated lower respiratory tract infections beginning in infancy. The prevalence, nature and control of human regulatory responses to MPV are unknown. In this study, we develop and optimize systems to evaluate MPV-driven cytokine responses. Using primary culture of human PBMC from previously exposed adults, MPV-stimulated responses were directly compared with those elicited by genetically and clinically similar respiratory syncytial viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
(66 reference statements)
4
25
0
Order By: Relevance
“…142 However, PBMCs, from healthy adults, stimulated with heat-inactivated hMPV promotes the induction of high levels IL-6 (a T H 2 polarizing cytokine that prevents T H 1 differentiation 143 ) and low levels of IFN-g and CCR5 (T H 1 cytokines) when compare with hRSV-stimulated PBMCs, thus suggesting a polarization toward a T H 2 response. 144 In contrast, other studies demonstrate that infants undergoing hMPV infection presented lower levels of pro-inflammatory cytokines compare with infants undergoing hRSV or influenza infection, including TNF-a and IL-1b, two cytokines related to the chemotaxis of neutrophils in lungs, as well as IL-12, IL-6 and IL-8. 145 Furthermore, in infants undergoing hMPV infection it was observed that a predominant T H 1 response is generated, since it was detected an increase in the IFN-g/ IL-4 ratio in nasal airway secretions.…”
Section: Adaptive Immunity Triggered By Hmpvmentioning
confidence: 58%
See 1 more Smart Citation
“…142 However, PBMCs, from healthy adults, stimulated with heat-inactivated hMPV promotes the induction of high levels IL-6 (a T H 2 polarizing cytokine that prevents T H 1 differentiation 143 ) and low levels of IFN-g and CCR5 (T H 1 cytokines) when compare with hRSV-stimulated PBMCs, thus suggesting a polarization toward a T H 2 response. 144 In contrast, other studies demonstrate that infants undergoing hMPV infection presented lower levels of pro-inflammatory cytokines compare with infants undergoing hRSV or influenza infection, including TNF-a and IL-1b, two cytokines related to the chemotaxis of neutrophils in lungs, as well as IL-12, IL-6 and IL-8. 145 Furthermore, in infants undergoing hMPV infection it was observed that a predominant T H 1 response is generated, since it was detected an increase in the IFN-g/ IL-4 ratio in nasal airway secretions.…”
Section: Adaptive Immunity Triggered By Hmpvmentioning
confidence: 58%
“…26 This impairment may contribute to a delayed T H 1 response. Indeed, CD4 C T cells elicit a poor IFN-g response when activated with hMPV-infected human peripheral blood mononuclear cells in vitro, 144 suggesting that these hMPV-infected cells can also inhibit the function of CD4 C T cells to stimulate an efficient antiviral T H 1 immune response in humans. The impairment of T cell immunity could be the result of impaired DC functions by hMPV, possibly through of a soluble factor derived from hMPV-infected DCs, as supernatants from these infected cells impairs T cells activation when stimulated by plate-bound antiCD3e and anti-CD28.…”
Section: Cd4mentioning
confidence: 99%
“…When specifically compared with RSV infection, however, the cytokine profile of hMPV is unique in some aspects. First, lower levels of TH 1 cytokines (particularly interferon-␥, tumor necrosis factor-␣, and macrophage inflammatory protein 1␣) are observed compared with RSV infections (20,23,24). Changes in IL-6, however, have been variably reported, with both higher (23) and lower (24) levels being reported after hMPV infections in humans.…”
Section: Human Metapneumovirusmentioning
confidence: 95%
“…We evaluated whether immature mouse DCs are permissive to hMPV infection by inoculating DCs with variable amounts of infectious (MOI [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and UV-inactivated hMPV (UV-hMPV). After inoculation, DCs expressing the fusion and nucleoprotein of hMPV could be easily identified by fluorescence microscopy among other noninfected DCs (Fig.…”
Section: Hmpv Infects Mouse Dcsmentioning
confidence: 99%
“…6,7 These findings suggest that hMPV may have evolved molecular mechanisms to evade host immunity and prevent immune clearance. [8][9][10][11][12] Dendritic cells (DCs) are professional antigen-presenting cells with the unique capacity to activate naive T cells, which later will exert an anti-viral immune response. [13][14][15] Priming of T cells requires DCs to efficiently capture and present viral proteins as antigenic peptide-MHC complexes and to provide co-stimulatory signals needed for full T-cell activation.…”
Section: Introductionmentioning
confidence: 99%